A Low Cost Microwave Synthesis Method for Preparation of Gold Nanoparticles - Thanh, Ngo Vo Ke; Giang, Nguyen Dang; Vinh, Lam Quang; Dat, Huynh Thanh (Communications in Physics, 2014)
Gold nanoparticles are being used in various biomedical applications due to their small size to volume ratio, extensive thermal stability, less toxic… Many different techniques e.g. chemical, photochemical reduction and electrochemical, gamma have been applied to preparing this nanoparticle. In this paper, we are developing a low-cost technique by using a common microwave system with medium power for synthesizing gold nanoparticles with using sodium citrate (Na3Ct) reduction in chloroauric acid (HAuCl4.3H2O). It was found that the comparing with normal thermal method, the reaction by the microwave irradiation was much faster. Besides, the effects the sodium citrate concentration and optical properties of gold nanoparticles were studied. The optical properties of gold nanoparticles suspension were characterized by using transmission electron microscopy (TEM), X-ray diffraction (XRD), and UV-VIS absorption spectroscopy (UV-Vis). Maximum absorbance wavelengths ( λmax ) for gold nanoparticles are 518-524 nm with the size of 12-25 nm. The size of gold nanoparticles decreases with increasing concentration of sodium citrate. Besides, the morphology of gold nanoparticles have a spherical shape with face-centered-cubic (fcc) crystalline structure.